Adsorption of Acid Red 18 by Activated Carbon Prepared from Cedar Tree: Kinetic and Equilibrium Study - M. R. Samarghandi; D. Izadi; M. Noori Sepehr; M. Zarrabi (Bihdād, 2012)
Introduction: Textile effluents are one of the main environmental pollution sources and contain toxic compounds which threat the environment. For that reason, the activated carbon prepared from Cedar Tree was used for removal of Acid Red 18 as an Azo Dye. Material and Methods: Activated carbon was prepared by chemical activation and was used in batch system for dye removal. Effect of various experimental parameters such as pH (3 to11), initial dye concentration (50, 75 and 100 mg/L), contact time (1 to 120 min) and adsorbent dosage (2 to 10 g/L) were investigated. Equilibrium data was fitted onto Langmuir and Freundlich isotherm model. In addition, pseudo first order and pseudo second order models were used to investigate the kinetic of adsorption process. Results: Results shows that dye removal was increase with increase in adsorbent dosage, contact time and initial dye concentration. In addition, higher removal efficiency was observed in low pH (pH=3). At 120 min contact time, pH=3, 6 g/L adsorbent dosage and 100 mg/L of initial dye concentration, more than 95% of dye was removed. Equilibrium data was best fitted onto Freundlich isotherm model. According to Langmuir constant, maximum sorption capacity was observed to be 51/28 mg/L. in addition pseudo second order model best describe the kinetic of adsorption of Acid Red 18 onto present adsorbent. Conclusion: The results of present work well demonstrate that prepare activated carbon from Pine Tree has higher adsorption capacity toward Acid Red 18 Azo dye and can be used for removal of dyes from textile effluents.